Evaluation of a pre-professional pathway program: perspectives of former students in the rural pre-medicine program at Selkirk College - McEwen, Sara; Vanderhoek, Jonathan; Larsen, Takaia (Canadian Medical Education Journal, 2023)
Background: Having a rural background is one of the most predictive factors in eventually having a rural practice, but people from rural areas face several barriers to post-secondary education. Pre-professional rural pathway initiatives are a potential solution. The Rural Pre-Medicine Program (RPM) at Selkirk College, British Columbia was developed to provide students with the credits necessary to apply to medicine and other health professional programs, an introduction to rural healthcare issues, and a unique and comprehensive support program to enable success. Methods: We administered a cross-sectional survey to former students who left the program from its inception in September 2014 to May 2020 to explore the extent to which program aims are being met. Results: The response rate was 49.4% (40/81). Respondents agreed the program increased their skills, their understanding of rural healthcare issues, and enhanced their competitiveness for applying to health professional programs. Most agreed the program increased their future rural work intentions. Respondents suggested that academic programming be more flexible to allow for more varied post-program pathways. Conclusion: This survey provides preliminary evidence the RPM Program is on track to increase the number of people with a rural affinity who prepare to become health professionals.